Effect of Teacher Autonomy Support on College Students’ Autonomous Motivation in Physical Education: The Mediating Role of Self-Efficacy - Qi Guo; Shamsulariffin Samsudin; Mohd Aswad Ramlan; Xiaofei Lin; Yubin Yuan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This is important not only for sustaining but also for further improving educational effectiveness. It has also been suggested that teacher autonomy support constitutes one critical environmental factor contributing to the development of this kind of motivation. However, related research in physical education contexts is still scant. The objective of this study was to find out how much personal support helped Chinese college students be more motivated to do well in physical education classes and how much this was due to self-efficacy playing a role. This study sampled 406 Chinese college students to collect data on perceptions toward teacher autonomy support, autonomous motivation, and self-efficacy in physical education settings. The two theoretical models analysed data using different statistical techniques to test mediated effects. Results showed that teacher-provided autonomy support, self-efficacy, and autonomous motivation are highly interrelated. Moreover, autonomy support predicts autonomous motivation indirectly through self-efficacy. In addition, the mediation model did not vary across gender groups. These findings suggest that physical educators can create increases in students' self-efficacy and autonomous motivation by enhancing the levels of autonomy support. This could lead to better quality in physical education and help people come up with effective methods to help students who are having trouble with their classes at the college level.